Use of artificial tears in cases of allergic conjunctivitis - D. Yu. Maycuk; L. B. Chilingaryan; I. A. Pronkin; A. R. Grigoryan (Oftalʹmologiâ)
Purpose: to evaluate the effectiveness of artificial tears use, particularly Ophtolique eye drops in cases of allergic conjunctivitis.Methods: 2 groups (30 patients each) with allergic conjunctivitis and complains for tearing were observed. Shirmer and Norn tests, lissamine and fluorescein staining were performed weekly during 21 day period. All patients were receiving standard anti-allergic treatment, but in 2-nd group the artificial tears were administered.Results: Mean time for allergic symptoms cure in 1-st group were — 16 days, fluorescein staining was 2.5 points, lissamine stain- ing was 4.8 points. 7 patients still had complains on tearing an foreign body feeling. In 2-nd group time of symptoms reveal was 13 days, fluorescein staining was 1.0 points, lissamine staining was 5.0 points. 3 patients had some complains.Conclusion: the inclusion of artificial tears in therapy of allergic conjunctivitis reduces the time of therapy and provides betterregeneration of the cornea.